Holistic Competency for Pesantren Caregivers: Bibliometric Evidence and a Maqasid-Based Framework - Bangun Sarwo Aji Wibowo; Suyatno (Contemporary Education and Community Engagement (CECE), 2026)
Pesantren dormitory caregivers (musyrif/musyrifah) bear a 24-hour guardianship role for nearly 4.9 million santri across Indonesia, yet no holistic competency model explicitly rooted in Maqasid al-Shariah has been developed to date. This article presents two complementary contributions: bibliometric evidence of a critical research gap, and a conceptual framework responding to that gap. Bibliometric analysis of the Dimensions database across nine progressive search stages (2001-2025) confirmed zero publications integrating Maqasid al-Shariah with pesantren caregiver competency development. The proposed framework maps seven holistic competency dimensions onto the Five Maqasid through an interdisciplinary approach, developed within a Design-Based Research (DBR) methodology. This article fills a critical conceptual gap while offering a constructive research agenda for pesantren caregiver human resource development in Indonesia, with direct implications for policy, caregiver training, and future empirical validation through DBR.